Teks Satua Galuh Payuk Analisis Sosiologi Sastra - Yanthi, Ni Putu Dian Kartika; Rai Putra, Ida Bagus; Sutama, Putu (Humanis; Vol 25 No 1 (2021), 2021)
This research discusses about Bali’s literature work purwa or traditional which shaped in satua with title “Satua Galuh Payuk text: Analysis of Sociology Literature”. The research purpose is to knowing the shaped structure and narrative structure also the social aspects which included in the satua itself. This research is using the theoretical structure and sociology approaching. Those theories used by combining some opinions from the literature experts. The method of this research on providing the data was through observation and heeding, on data analysis the researcher was used qualitative method. The method on providing the result of data analysis the researcher was used the informal method. For supporting all of the methods that have been used the researcher used some techniques which are: recording, transliteration translating, analytic descriptive, and deductive inductive. The results of this research is the shape structure and the narrative structure from “Satua Galuh Payuk Text”. The shape structure includes the language styles and diction and the narrative structure includes: incident, plots, background, figure and characterization, theme and mandate. Besides, this research was also analyzed the social aspects which become objects from the research which are naming, love aspect, civilization aspect, leadership aspect, religion aspect which consist of philosophical aspect, moral aspect and ceremony aspect.